The Implementation Right To Attain Second Opinion Patient Of National Health Insurance Participant - Muhammad Ikhsan Lukman; Slamet Sampurno; Amir Ilyas (Faculty of Law, University of Mataram, 2018)
This research is empirical juridical research. The research material consists of the primary and secondary data. Primary Data are gained from research subject, whilst secondary data are obtained from document study, this research is analyzed with the qualitative method and explained descriptively. The research result is attained that the law protection design is given by RSUD Haji Makassar with determining the operational procedure standard of patient right poured forth in the Director SK Number 29.02.08 About The Patient Right and Family to consult about disease matter from patient to another doctor is a law protection form preventively which the accusation service and sigh from patient poured forth the Director SK Number 155/TU/RSUD/I/2016 related to the operational procedure standard (SPO) Handling Sigh/Accusation Customer, that SPO is a repressive law protection form. Right implementation obtains the second opinion in RSUD Haji Makassar is not well-implemented maximumly, it is caused by no BPJS Kesehatan regulation accommodating patient right to gain the second opinion.